2003
DOI: 10.1002/food.200390095
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glutathione peroxidase activity in human milk

Abstract: An analytical method for determining glutathione peroxidase (GPx) (EC 1.11.1.9) activity in whole blood has been adapted to human milk samples. The values obtained for precision (relative standard deviation: 8.4%), linearity and accuracy (recovery: 90.4%) indicate the adequacy of the method for the mentioned purpose. The method was applied to 11 human milk samples obtained in the range from 6 to 135 days post partum. The resulting GPx activities (83.3 +/- 23.6 U/L) did not correlate to the selenium content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The mean GPx activity obtained was inferior to that reported by our group in earlier studies (22). Other authors have evaluated glutathione peroxidase activity in human (25,28,29), but no comparison can be made with our own findings, since the literature expresses enzyme function in terms of the amount of enzyme present, while in our work the units used correspond to enzyme activity.…”
Section: Discussionmentioning
confidence: 89%
“…The mean GPx activity obtained was inferior to that reported by our group in earlier studies (22). Other authors have evaluated glutathione peroxidase activity in human (25,28,29), but no comparison can be made with our own findings, since the literature expresses enzyme function in terms of the amount of enzyme present, while in our work the units used correspond to enzyme activity.…”
Section: Discussionmentioning
confidence: 89%
“…It is interesting that selenium supplementation of Chinese women with habitually low selenium intake increases plasma selenium, plasma glutathione peroxidase activity and milk selenium, but not milk glutathione peroxidase activity. 21 It was also confirmed that GSH-Px activities in milk did not correlate with the selenium content of the samples, 22 thus indicating a crucial role of GSH-Px in control of hydrogen peroxide in human milk. A study of selenium deficiency in Serbia showed that selenium deficiency is present, 23 but it also had no effect on GSH-Px activity in preterm milk.…”
Section: Resultsmentioning
confidence: 94%
“…Activity determination of GSHPx used the previous method. [13,14] The activity of GSHPx is shown in Figure 5.…”
Section: Gshpx Activity Determinationmentioning
confidence: 99%